The Instructional Design For The Teaching English At Smp Rimba Teruna Randublatung, Blora: A Naturalistic Study - Suciati, Ari; , Prof. Dr. Endang Fauziati, M. Hum; , Agus Wijayanto, Ph.D (2015)
English has become major device as a bridge of international communication. The existence of instructional design is a recent issue in English teaching particularly at Junior High School. The problems of the research are: the instructional design for the teaching English at SMP Rimba Teruna Randublatung, Blora. The objectives of the research reveal briefly of instructional design for the teaching English at SMP Rimba Teruna Randublatung, Blora which encompasses syllabus, learning objective, classroom procedure and technique, instructional material, media used by the English teacher, assessments model, and students opinion about the teachers' instructional media, method of teaching, assessment used by the English teacher. The research belongs to a naturalistic study. Depart to the underlying theories and the data taken from the document, the syllabus of SMP Rimba Teruna RanduBlatung, Blora called as notional functional syllabus. The principal highlighting of syllabus is upon communicative purpose and conceptual meaning of language in novice, elementary and intermediate level. The learning objectives categorized into two namely, general objectives and specific objectives. The classroom procedure has two patterns namely: BKOF-MOT-JCOT-ICOT and BKOF-MOT-ICOT. The classroom techniques comprises several techniques: reading aloud, group discussion, dialogue performance, question and answer, explicative reading. The instructional material were divided into four categories: printed material, audio material, visual material, and material taken from internet. Media which are used by the English teacher are as follows: text book and whiteboard, LCD, internet and picture. The teachers use many assessment models namely: multiple choice forms, essays, matching, oral performance (presentation), composing group, Formative assessment, and summative assessment. There are students' opinions about the teachers' instructional media, method of teaching, assessment used by the English teacher. They also state opinion about the teacher way of giving them motivation and for the better of the teacher teaching. Departing with the finding, discussion, conclusion and implication, the writer suggests for the English teacher to encourage students' engagement to study in the classroom. The application of diverse methods and techniques are obviously required in English teaching. The writer also recommends for the future researcher to expand the study in other research field